CONSTRUCTION OF UNDERSTANDING IN VIEWING NATIONAL SOVEREIGNTY OVER MINERAL AND COAL RESOURCES - Nordiana Nordiana; Asnar Asnar; Suryaningsi Suryaningsi; Endang Herliah (European Journal of Humanities and Educational Advancements, 2024)
Understanding as a person’s level of knowledge and awareness of a particular concept, topic or issue. In the context of this article, understanding refers to students’ level of knowledge regarding national sovereignty over mineral resources, such as coal, and how it can influence their critical thinking on related issues. The aim of the research is to construct students’ understanding of viewing national sovereignty to improve critical thinking. Using a qualitative type of research with a descriptive approach, through interviews in collecting data followed by a triangulation method to measure the validity of the data. This technique makes it easier for researchers to collect the necessary data. The conclusion is that a balanced educational approach is needed, between students’ knowledge, understanding and actions. Students’ understanding before receiving learning was still lacking, but after being given material through learning it changed. They have even prepared themselves to become actors in managing coal as the largest source of wealth.